Desain Formulir Edukasi Pasien dan Keluarga Berbasis Elektronik Guna Menunjang Pelaksanaan Sistem Rekam Medis Elektronik - Firmansyah, Muhammad Fadjar; Sufyana, Candra Mecca; Suryani, Ade Irma (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Patient and family education forms are documents designed to provide information to patients about certain aspects related to health, treatment, or medical procedures that aim to increase the patient's understanding of their health condition, actions to be taken, and steps that need to be taken . Patient and family education forms at one hospital in Bandung City are still manual or conventional. This research aims to design an electronic-based patient and family education form to support the implementation of the move from manual medical records to electronic medical records and make it easier for officers to fill in data on patient education forms effectively and efficiently. The methods for collecting research data used include literature study, interviews, and observation with qualitative analysis. The system development method used in this research is the waterfall method. The result of this research is a design for an electronic-based patient and family education form. So, with this system, it is hoped that it can improve the quality of health services in hospitals and build the implementation of an electronic-based medical record system as regulated by Minister of Health Regulation Number 24 of 2022.